AI-Driven Robotic Arm for Medical Surgeries - Rama Subbanna (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Artificial intelligence (AI) applications in medical robotics are ushering in a new epoch in medicine. Advanced medical robots are capable of executing diagnostic and surgical operations, facilitating rehabilitation, and offering symbiotic prostheses to substitute missing limbs. The technology used in these devices, including computer vision, medical image analysis, haptics, navigation, precise manipulation, and machine learning (ML), may enable autonomous robots to do diagnostic imaging, remote surgery, surgical subtasks, or whole surgical operations. Furthermore, artificial intelligence in rehabilitation devices and sophisticated prostheses may provide personalized assistance, along with enhanced functioning and mobility (refer to the image). The amalgamation of remarkable advancements in robotics, medicine, materials science, and computers may yield safer, more efficient, and more accessible patient care in the future.